EFEKTIVITAS MEDIA PEMBELAJARAN BERBASIS HANDPHONE ANDROID DALAM PEMBELAJARAN FIKIH DI MAN 1 MEDAN - Manungkalit, Khoirunnisa; Dahlan, Zaini (Program Studi Pendidikan Agama Islam Tarbiyah IAI Muhammadiyah Bima, 2026)
In today's digital era, technology integration in education is becoming increasingly important to improve the quality of learning and student engagement. This study aims to evaluate the use of digital media in religious learning, specifically in the Fiqh subject at Madrasah Aliyah Negeri (MAN) 1 Medan. This study used a descriptive qualitative approach by collecting data from primary and secondary sources to gain comprehensive insights. The results show that the use of digital media in the Fiqh subject at MAN 1 Medan has been implemented effectively. The school has provided supporting facilities, such as a computer laboratory and adequate internet services, which greatly assist students and teachers in accessing and utilizing digital media for the learning process. The use of digital media allows for increased student interaction and engagement in understanding the Fiqh material more deeply. In addition, the use of digital media also makes it easier for teachers to deliver material in a more interesting and interactive manner. For further research, it is recommended to expand the variables with a more innovative approach and use this study as a reference in developing digital-based learning strategies in madrasas.